2006
DOI: 10.1080/14459790600644093
|View full text |Cite
|
Sign up to set email alerts
|

Problem Gambling and Gaming Machine Density: Socio-spatial Analysis of Three Victorian Localities

Abstract: This paper examines the debate about possible relationships between problem gambling and accessibility to electronic gaming machines (EGMs), in the context of the Victorian Government's policy that imposed a 'cap' on EGMs in disadvantaged communities. Using GIS (Geographical Information Systems), the spatial distribution of social disadvantage in three 'capped' localities was compared with the spatial distribution of gaming venues and patterns of concentrated EGM expenditure during 2001-2005, including seasona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 7 publications
(9 reference statements)
3
29
0
Order By: Relevance
“…First, gambling venues in this study were predominantly located in low socio-economic areas, a finding that is consistent with trends reported in both the Australian (Young et al, 2012a;McMillen & Doran, 2006) and international literature (Pearce, Mason, Hiscock, & Day, 2008;Wheeler, Rigby, & Huriwai, 2006). This poses a significant challenge for public health authorities given the harms associated with gambling for vulnerable populations, including those from low socioeconomic backgrounds (Welte, Wieczorek, Barnes, Tidwell, & Hoffman, 2004;Welte, Wieczorek, Barnes, & Tidwell, 2006).…”
Section: Discussionsupporting
confidence: 76%
“…First, gambling venues in this study were predominantly located in low socio-economic areas, a finding that is consistent with trends reported in both the Australian (Young et al, 2012a;McMillen & Doran, 2006) and international literature (Pearce, Mason, Hiscock, & Day, 2008;Wheeler, Rigby, & Huriwai, 2006). This poses a significant challenge for public health authorities given the harms associated with gambling for vulnerable populations, including those from low socioeconomic backgrounds (Welte, Wieczorek, Barnes, Tidwell, & Hoffman, 2004;Welte, Wieczorek, Barnes, & Tidwell, 2006).…”
Section: Discussionsupporting
confidence: 76%
“…The low levels of reported gambling problems for non-remote locations in Western Australia was unsurprising as this is then only jurisdiction that does not supply EGMs, the most harmful form of gambling, outside of the casino in Perth (see Map in Fig. 1) (McMillen and Doran 2006;Queensland Government 2005;Young et al 2007;Young et al 2008a). The high estimates of reported gambling problems in remote regions, particularly in the Northern Territory and Queensland, may indicate that unregulated gambling (i.e.…”
Section: Estimates Of Reported Gambling Problemsmentioning
confidence: 80%
“…This is significant given that the limited data available from national and state level surveys indicate that participation in regulated gambling by Indigenous people is no different to the general Australian population (McMillen and Donnelly 2008;Productivity Commission 1999;Young et al 2007). EGM play, the activity most associated with problem gambling in Australia, has consistently been identified as the most popular activity for Indigenous people (Dickerson et al 1995;McMillen and Doran 2006;Queensland Government 2007;Young and Stevens 2009;Young et al 2008b). Two of these studies found that regular (at least weekly) gamblers spent on average between 20 and 30% of their income on gambling (Dickerson et al 1995;Holden et al 1996).…”
Section: Indigenous People and Regulated Gamblingmentioning
confidence: 96%
“…For example, in the case of electronic gaming machines (EGMs), while there is variation at the local scale of analysis (McMillen and Doran 2006), a negative relationship between the number of machines in a particular areas and the its socioeconomic status has been consistently identified (Doran et al 2007;Marshall 1999;Marshall 2005;Marshall and Baker 2001a;Marshall and Baker 2001b;Marshall and Baker 2002;Marshall et al 2004;Productivity Commission 1999;South Australian Centre for Economic Studies 2005). In other words, gambling participation is socially patterned in that different social groups are likely to gamble on specific gambling modes which in turn generate particular problem gambling outcomes.…”
mentioning
confidence: 96%